ANALISIS STRATEGI PEMASARAN PADA TOKO BUAH MONIC KOTA CURUP - M. Fachrurrozy Fachrurrozy; Onsardi Onsardi (Yayasan Insani Mandiri Santani, 2025)
This research aims to analyze the marketing strategies implemented by the Monic Fruit Shop in Curup City to increase sales and strengthen its position in the local market. The method used in this research is a SWOT analysis which identifies the strengths, weaknesses, opportunities and threats faced by the store. The results of this research can be concluded that the results of the IFAS matrix calculation are the weighted score for the strength factors, namely 2.17 IFAS overall weakness factors with an average score of 1.82, indicating that the strength factors are stronger than the weakness factors. The result of the EFAS matrix calculation is that the weighted score for the opportunity factor is 2.24. and threats, the overall results obtained from EFAS with an average score of 0.1.75 indicate that the opportunity factor is stronger than the threat factor. The results of the SWOT analysis of marketing strategies to increase sales of the Monic Fruit Shop were the strengths-opportunities strategy because it had a combined SWOT strategy value (4.41) higher than the weaknesses-Opportunities strategy (4.06), strengths-threats strategy (3 .92) weakness-threat strategy and purn (3.57). Marketing Strategy to Increase Sales of the Monic Fruit Shop in Curup City. The marketing strategy carried out by the Monic Fruit Shop in Curup City to increase sales involves utilizing existing strengths and taking advantage of available opportunities. In this case, Monic Fruit Shop can optimize promotional strategies through existing social media to expand market reach. Keywords: Marketing Strategy, EFE Matrix, IFE Matrix, SWOT Matrix.